IN VITRO ANTIBIOFILM ACTIVITY OF GYMNEMA SYLVESTRE EXTRACT AGAINST BIOFILM FORMING STREPTOCOCCUS PYOGENES FROM UPPER RESPIRATORY TRACT - J, Dineshbabu; P, Srinivasan; K, Manimekalai; D, Teepica Priya Darsini (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study was aimed to evaluate the antibiofilm activity of Gymnema sylvestre solvent extracts against the biofilm forming Streptococcus pyogenes strains SP-1 and SP-2 isolated from pharyngitis patients. Methods: The study involved the determination of minimum inhibitory concentration (MIC) and biofilm inhibitory concentration using microtiter plate method, growth curve analysis using spectrophotometry, antibacterial activity using agar well-diffusion method and light microscopic analysis of S. pyogenes biofilms treated with the plant extracts. Results: Biofilm inhibition assay was showed that the G. sylvestre methanol and ethyl acetate extracts inhibited biofilms at sub-MIC which was also confirmed via light microscopy. Minimal inhibition concentration against the tested pathogens was observed at 4 mg/ml for both methanol and ethyl acetate extracts. The antibacterial and growth curve analysis showed no significant inhibition at the concentration below MIC. Conclusion: This study is an attempt to highlight G. sylvestre as a novel antibiofilm source, as the plant is well known for its biologically active components. Identification and can develop a scientific base for the use in modern medicine. Keywords: Antibiofilm, Biofilm inhibitory concentration, Gymnema sylvestre, Streptococcus pyogenes.